2023
DOI: 10.1021/jacsau.3c00482
|View full text |Cite
|
Sign up to set email alerts
|

Defect and Donor Manipulated Highly Efficient Electron–Hole Separation in a 3D Nanoporous Schottky Heterojunction

Chunyu Yuan,
Hongfei Yin,
Huijun Lv
et al.

Abstract: Given the rapid recombination of photogenerated charge carriers and photocorrosion, transition metal sulfide photocatalysts usually suffer from modest photocatalytic performance. Herein, S-vacancy-rich ZnIn2S4 (VS-ZIS) nanosheets are integrated on 3D bicontinuous nitrogen-doped nanoporous graphene (N-npG), forming 3D heterostructures with well-fitted geometric configuration (VS-ZIS/N-npG) for highly efficient photocatalytic hydrogen production. The VS-ZIS/N-npG presents ultrafast interfacial photogenerated ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…64,65 Following the ZnI 2 IP treatment, the diameter significantly decreased, suggesting reduction in the resistance of the device. 64,66 These IS measurement results revealed that the ZnI 2 IP can reduce interfacial defects and trap states, 65 enhancing the electrical connectivity between CIS-ZnI 2 -QDs and ZMO ETL layers, consequently reducing the complex resistance of the overall LED devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 Following the ZnI 2 IP treatment, the diameter significantly decreased, suggesting reduction in the resistance of the device. 64,66 These IS measurement results revealed that the ZnI 2 IP can reduce interfacial defects and trap states, 65 enhancing the electrical connectivity between CIS-ZnI 2 -QDs and ZMO ETL layers, consequently reducing the complex resistance of the overall LED devices.…”
Section: Resultsmentioning
confidence: 99%
“…Next, to investigate the impact of ZnI 2 IP at the QD-ETL interface, we conducted impedance spectroscopy (IS) measurements to assess the electrical connectivity of the two layers (i.e., CIS-QD and ETL layers) in the QLED devices (Figure G. As depicted in Figure G, the Nyquist plots for both the CIS-ZnI 2 -QLED and ZnI 2 -IP-treated CIS-ZnI 2 -QLED (denoted as CIS-ZnI 2 -IP-QLED) devices showed a semicircle shape, indicative of an RC circuit consisting of a resistor (R) and a capacitor (C) within the device. , Following the ZnI 2 IP treatment, the diameter significantly decreased, suggesting reduction in the resistance of the device. , These IS measurement results revealed that the ZnI 2 IP can reduce interfacial defects and trap states, enhancing the electrical connectivity between CIS-ZnI 2 -QDs and ZMO ETL layers, consequently reducing the complex resistance of the overall LED devices.…”
Section: Resultsmentioning
confidence: 99%
“…This study underscores the utilization of an ML approach in materials science research, and regarding this, the RNN-based LSTM model demonstrates effectiveness in predicting and forecasting the stability of photoanodes. Any observed decline in photoanode stability can likely be attributed to factors such as corrosion, material degradation, or surface passivation . Overall, the developed photoanodes exhibit robust stability over time, rendering them suitable for efficient PEC performance.…”
Section: Resultsmentioning
confidence: 99%
“…8(e)-(h)). 64 It was observed that the energy levels of C 1s and N 1s orbitals on the surface of CS/TA-10 moved towards low binding energy under light illumination, while the orbital energy levels of S 2p and Cd 3d orbitals moved towards high binding energy due to the formation of Schottky heterojunctions between CdS and TA-GDY. In the presence of light, the photoexcitation of CdS leads to the separation of photogenerated electrons from holes and the transfer of photogenerated electrons from the valence band to the conduction band.…”
Section: Photocatalytic Performance Analysismentioning
confidence: 96%